ANALYSIS OF LIQUIDITY RATIO AS AN ASSESSMENT TOOL FOR FINANCIAL PERFORMANCE AT PT BANK MANDIRI (PERSERO) Tbk (2019-2023) - Juliana, Widya Ika; Yuliusman, Yuliusman; Hernando, Riski (Faculty of Economics and Business Universitas Jambi, 2025)
This study aims to analyze the liquidity ratio as a tool to measure financial performance at PT Bank Mandiri (Persero) Tbk. The research applies a descriptive qualitative approach, focusing on financial reports from 2019 to 2023. Liquidity ratio analysis is considered important because it shows the bank’s capability to meet short-term obligations or liabilities that have matured. Through this analysis, the study seeks to provide a clear picture of how well PT Bank Mandiri manages its liquidity during the observed period. The ratio reflects the bank’s financial health, especially its ability to provide funds quickly to fulfil customer withdrawals, loan disbursements, and other short-term commitments. By using this approach, the study can evaluate financial stability and performance without relying on complex statistical models. The findings are expected to give insights into the bank’s effectiveness in liquidity management and its overall resilience in facing financial challenges. Keywords: Financial Statements, Liquidity Ratio.